Audit of medication interventions made on the Paediatric Intensive Care Unit (PICU). Issue 6 (9th May 2013) - Canavan, E; Sutherland, A
Abstract : Aims: Medication errors within a paediatric setting are thought to be more common than in adults, and may be as high as 1 in every 6.4 prescriptions. 1 A 2010 audit of paediatric intensive care unit (PICU) found a prescribing error rate of 11.4%, with 92% of these being identified and corrected by the PICU pharmacist but only 24% were intercepted before administration. Conversely, there have been a number of critical incidents reported within paediatric critical care concerning inappropriate dosage changes that have adversely affected patient care. The aim of this audit was to determine the number of interventions made to prescriptions for medications within PICU, to assess the appropriateness of these interventions based on the professional judgement of the PICU pharmacist and to identify who was making the interventions. This audit will benchmark the standards for further audits. Interventions could be made by any doctor, nurse or pharmacist caring for patients on PICU. Interventions must be justified and in the best interests of the patient. Interventions should be documented in terms of what was changed, why it was changed, who recommended the change and what time the change was made. An intervention was defined as: Any change to an order for medication by rewriting, editing, obscuring or amending a prescription in any way. Method: A prospective, observational audit of interventions made to medications on PICU. The population audited were all paediatric patients admitted or present on PICU and prescribed any medication from 02 April 2012 to 04 May 2012. Results: During the audit 82 medication interventions were recorded, of these 54.9% were made by pharmacists and 28% by nurses. Of the 82 interventions that were audited, 71 were deemed to be appropriate and 10 were deemed to be inappropriate; the appropriateness of 1 of the interventions was undetermined. The majority of interventions were made between the hours of 9:00 h–17:00 h on weekdays, during this period pharmacists made 68.3% of interventions and fewer inappropriate interventions were made. The majority of inappropriate interventions were made during the night, with the most common inappropriate intervention deemed to be changing of dose timings. The most common medications with interventions were antibacterials and antivirals, with the most common intervention being stopping medications. Conclusions: Medication interventions occur frequently within the PICU setting and are initiated by all members of staff. However not all of these interventions are appropriate for patients. Of the 82 interventions made 86.6% were deemed to be appropriate. Of those deemed to be inappropriate, the reasoning behind them has yet to be analysed. Defining appropriateness is a qualitative exercise and further work must be undertaken to assess the perception of appropriate and inappropriate interventions. It is proposed that a 2-round Delphi method is used to test the appropriateness of the questioned interventions. This should help define what is an inappropriate intervention and allow for recommendations to be made to prevent these from occurring.